2019
DOI: 10.1111/tmi.13192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of methicillin‐resistant Staphylococcus aureus in the Brazilian primary health care system

Abstract: Objective To evaluate the molecular epidemiology and to georeference Staphylococcus aureus isolated from wounds and nares of patients seen at Basic Health Units (BHUs) of a Brazilian city. Methods Observational, cross‐sectional study conducted from 2010 to 2013. A total of 119 S. aureus strains isolated from the wounds and nares of 88 patients were studied. The isolates were characterised by identifying virulence genes encoding enterotoxins A–E, haemolysins α, β and δ, exfoliatins A, B and D, biofilm productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…However, SCCmec types I and II were also detected, which are commonly found circulating in health services. This fact has also been reported by Pereira-Franchi et al [62] and Silveira et al [69] who found a higher prevalence of isolates harboring SCCmec type II, which was attributed to a history of hospitalization.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, SCCmec types I and II were also detected, which are commonly found circulating in health services. This fact has also been reported by Pereira-Franchi et al [62] and Silveira et al [69] who found a higher prevalence of isolates harboring SCCmec type II, which was attributed to a history of hospitalization.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth mentioning that patients in hospital-community settings, such as bedridden or institutionalized older adults with chronic infections, have a higher prevalence of SCCmec types I and II [62,69]; in addition, hospitalized patients frequently carry isolates that harbor SCCmec type III. These SCCmec are larger and carry plasmids and transposons with other resistance genes, often multidrug-resistant genes.…”
Section: Discussionmentioning
confidence: 99%
“…This fact reinforces the importance of throat colonization, which could be a route of transmission within the population studied. Other studies involving individuals from the same city and region also found MRSA ST5-SCCmec type IV and ST8-SCCmec type IV, suggesting that these strains are prevalent in the region [28,[38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the history of MRSA in Brazil will help to better understand the spread of this important pathogen in Latin America, as well as in the new world. In Brazil, there are some epidemiological surveillance systems of resistant bacteria which do not work at a national level [ 13 , 14 ]. However, in 2018, a program named PAN-BR (National Action Plan for the Prevention and Control of Antimicrobial Resistance in Brazil) was developed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 2010s, MRSA remained being increasingly reported in Brazil, as shown in Figure 4 . The most common clones in the hospital environment continued to be those carrying the SCC mec types II, III, and IV [ 14 , 65 , 73 , 102 , 103 ]. However, SCC mec type II, in contrast to the last decade, was reported as one of the most prevalent clone [ 103 109 ].…”
Section: Introductionmentioning
confidence: 99%